2018
DOI: 10.1080/17518423.2018.1434700
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breathing rate on the cardiac autonomic dynamics among children with cerebral palsy compared to typically developed controls

Abstract: The results of the current work present the immediate effect of paced breathing on HRV parameters in CP and TD children. Further studies are needed to investigate the effect of long-term treatment focusing on paced breathing for children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In 2014, Amichai and Katz-Leurer published a review based on the articles published between 1990 and 2013 assessing the function of the autonomic cardiac regulation among children with CP [10]. However, since that period, eight new articles in this area have been published [8,9,[11][12][13][14]54,56]. Amichai and Katz-Leurer concluded that there is a trend that children with CP suffer from impaired cardiac autonomic system regulation [10].…”
Section: Hrv Changes In Children With Cpmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2014, Amichai and Katz-Leurer published a review based on the articles published between 1990 and 2013 assessing the function of the autonomic cardiac regulation among children with CP [10]. However, since that period, eight new articles in this area have been published [8,9,[11][12][13][14]54,56]. Amichai and Katz-Leurer concluded that there is a trend that children with CP suffer from impaired cardiac autonomic system regulation [10].…”
Section: Hrv Changes In Children With Cpmentioning
confidence: 99%
“…Results of the articles published between 2013 and 2019 confirmed this trend, but also provided new findings (see Table 3). Authors of these studies suggested that children with CP present lower cardiac autonomic system adaptation to exercise and activity [8] and lower spirometry [12] compared to typically developed children; non-optimal HR reduction after a submaximal treadmill test indicating low reactivation of the parasympathetic system [11]; decreased values of selected time-domain HRV parameters in those dependent on adult assistance for mobility compared to those who are generally independent [14]. Israeli-Mendlovic et al [9] suggested and Cohen-Holzer et al [13] and Amichai et al [12] showed that some forms of physical exercises and training improve cardiac autonomic regulation in pediatric patients with CP by reducing HR and breathing rate and increasing values of selected HRV parameters.…”
Section: Hrv Changes In Children With Cpmentioning
confidence: 99%
See 3 more Smart Citations